Assessment of concrete deterioration of bridge substructures situated in Pasig River - Pulbosa, Joshua Philip S.; Viado, Maria Urduja Jean B.; Orozco, Christian R. (Quezon City College of Engineering, University of the Philippines Diliman, 2018)
The main purpose of the study is to assess the current deterioration condition of different concrete bridge substructures situated in the Pasig River and create a respective maintenance plan. These bridges are vital to the ease of access and transport through the city which is why early diagnosis of vulnerability is the key to ensuring the prevention of a structural disaster. The concrete surfaces of these substructures are exposed to polluted waters. Different researches analyzed the deterioration of concrete surfaces due to wastewater and showed that the compounds present in these polluted environments catalyze microbial degradation and weaken the structural integrity of concrete. It was also found that the progress of concrete deterioration is linear therefore longer exposure would result to greater damage. For the visual inspection, a sheet was generated by modifying the ACI 201.1 R-08 (Guide for Conducting a Visual Inspection of Concrete in Service) while the scoring sheet to be used in this research was adapted from the scoring system proposed by Coronelli. However, the procedure of Coronelli considers several factors that are non-existent in the Philippine condition such as freeze, thaw, etc. therefore the tool is further modified considering the local setting. Site visits on-foot and via ferry were done in conducting visual inspection and the analysis of the chosen bridges showed that 11 of the 13 bridges are in a deterioration class where there is a reduction of serviceability and durability. It was also noted that the large distance from an upstream bridge causes significant damage to the bridge substructure. Lastly, a maintenance plan was generated for each bridge using methods such as patching, epoxy coating, caulking, recasting, and many more.
Thesis (Bachelor of Science in Civil Engineering)--University of the Philippines Diliman
Keywords: Concrete bridges -- Deterioration; Bridges -- Philippines -- Pasig River (Luzon)